IMPLEMENTASI INTEGRASI API DALAM WORKFLOW AUTOMATION MENGGUNAKAN N8N UNTUK MENDUKUNG TRANSFORMASI DIGITAL - Ahmad Rifa’i; Ahmad Faqih; Muhamad Dadan Rifai; Fahmi Rahman (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This Community Service activity was carried out with the theme "Implementation of API Integration in Workflow Automation Using n8n to Support Digital Transformation." The target of this activity was vocational high school students throughout Cirebon City who needed to strengthen their digital competencies, especially in understanding system integration, workflow automation, and the use of technology-based applications. This activity was motivated by the needs of the modern workplace which increasingly demands vocational graduates to have the ability to use technology productively, understand data flows, and be able to develop simple digital solutions. The method of implementation of the activity was carried out through a hands-on workshop. Participants received material on digital transformation, the concept of APIs, webhooks, workflow automation, and the use of n8n. The activity continued with a demonstration of workflow creation, guided practice, development of school case studies, presentation of results, and evaluation. The case studies used included automation of activity registration, data storage to spreadsheets, participant recaps, and automatic notification sending. This approach made it easier for participants to understand technical concepts because the material was linked to real-life needs in the school environment. The results of the activity showed that participants were able to create simple workflows using n8n. Participants were able to understand the functions of triggers, nodes, data mapping, credentials, and outputs in the automation process. The satisfaction evaluation showed an average score of 4.50, categorized as very satisfied. The pre-test and post-test results also showed an increase in understanding from 58.25 to 83.40, representing a 25.15-point increase. These results indicate that the community service activity was effective in improving digital literacy and basic workflow automation skills. The activity outputs included training modules, practical worksheets, activity documentation, evaluation results, and simple workflow examples. This activity provided benefits to participants, accompanying teachers, and partner schools. Participants gained applied digital skills, and schools obtained technology-based learning resources. Overall, this activity supports the strengthening of the digital transformation of vocational education in Cirebon City.